Integrating handicapped and nonhandicapped preschool children: Issues in program development - Mary Kay Zabel (Educational Considerations, 1978)
Concern for the educational situation of pre-school children with special needs was evident in this country as early as 1930. In that year the White House Conference on Children, convened by President Hoover, issued a 'Children's Charter,' outlining the aims and goals held by the Conference.